PSIV-7 Effect of Biochar Supplementation in Beef Cattle Growing Diets on Greenhouse Gas Emissions. (7th May 2021) - Sperber, Jessica L; Troyer, Braden; Norman, Mitch; McPhillips, Levi J; Watson, Andrea K; Erickson, Galen E
Abstract: The objective of this experiment was to evaluate the impact of feeding biochar in a growing diet on cattle performance, methane (CH4 ) and carbon dioxide (CO2 ) emissions. Biochar was sourced from ponderosa pine wood waste (High Plains Biochar, Laramie, WY) and was 83% C with 426 m 2 /g surface area. Crossbred steers (n = 160; initial BW = 357 kg ± 44 kg) were utilized in a randomized block design (blocked by BW), steers assigned randomly to pen (n = 16), and pens assigned randomly to treatment. Two treatments were evaluated, a control (CON) without biochar (40% wheat straw, 40% corn silage, 15% modified distillers grains, 5% supplement) and the same diet with biochar included at 0.8% of diet dry matter replacing corn in the supplement (CHAR). Four pen replications per treatment were paired within BW block and rotated randomly through an emissions barn with two chambers (each treatment evaluated simultaneously) to capture average weekly CH4 and CO2 production. Pen was experimental unit and chamber was included as a fixed effect for emissions data. There were no statistical differences in performance outcomes between CHAR and CON steers (P ≥ 0.23). Numerically, average daily gain (ADG) was greater (P = 0.46) and dry matter intake (DMI) was lower (P = 0.23) for CHAR steers, resulting in a 2.8% improvement in feed efficiency for CHAR steers (P = 0.25). Emissions of CO2 and CH4 did not statistically differ between treatments (P ≥ 0.22). Numerically, CO2 and CH4 emissions were lower for CON compared to CHAR steers when reported as g per day (3.6% lower) or g per kg of DMI (2.4% lower). Based on the results from this study, there was no indication that feeding biochar, supplemented at 0.8% of diet, reduces GHG emissions in growing steers when compared to negative control.